2016
DOI: 10.1002/hyp.11052
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of the ecohydrological separation hypothesis in a semiarid catchment

Abstract: The ecohydrological separation hypothesis states that transpiration through plants and drainage to streams and groundwater are sourced from separate soil water pools, which possess distinct isotopic signatures. Evidence for ecohydrological separation has relied on the globally ubiquitous observation that plant water and draining water are isotopically distinct. We evaluated the ecohydrological separation hypothesis in the Dry Creek Experimental Watershed in the semiarid, snow-dominated landscape of southwest I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
99
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(103 citation statements)
references
References 41 publications
3
99
1
Order By: Relevance
“…This fractionation signal in the soil water was of the same magnitude as for surface waters in the peatland drainage network of a raised bog in the Bruntland Burn, where the lc-excess reached values < −5 ‰ and the EL slope ranged from 3.9 to 4.9 between May and September (Sprenger et al, 2017b). In comparison to arid and Mediterranean environments, where SW lc-excess can fall below −20 ‰ (McCutcheon et al, 2016, andreviewed in Sprenger et al, 2016b), the SW lc-excess in the Scottish Highlands remained relatively high. While the lc-excess was usually not significantly different from zero at 15-20 cm soil depth in the studied podzols of the study site, soils studied by McCutcheon et al (2016) in a much drier environment (Dry Creek, Idaho) showed that the SW lc-excess from the surface down to −70 cm was significantly lower than zero.…”
Section: Evaporation Dynamics Within the Soil-plant-atmosphere Interfacementioning
confidence: 53%
See 3 more Smart Citations
“…This fractionation signal in the soil water was of the same magnitude as for surface waters in the peatland drainage network of a raised bog in the Bruntland Burn, where the lc-excess reached values < −5 ‰ and the EL slope ranged from 3.9 to 4.9 between May and September (Sprenger et al, 2017b). In comparison to arid and Mediterranean environments, where SW lc-excess can fall below −20 ‰ (McCutcheon et al, 2016, andreviewed in Sprenger et al, 2016b), the SW lc-excess in the Scottish Highlands remained relatively high. While the lc-excess was usually not significantly different from zero at 15-20 cm soil depth in the studied podzols of the study site, soils studied by McCutcheon et al (2016) in a much drier environment (Dry Creek, Idaho) showed that the SW lc-excess from the surface down to −70 cm was significantly lower than zero.…”
Section: Evaporation Dynamics Within the Soil-plant-atmosphere Interfacementioning
confidence: 53%
“…In comparison to arid and Mediterranean environments, where SW lc-excess can fall below −20 ‰ (McCutcheon et al, 2016, andreviewed in Sprenger et al, 2016b), the SW lc-excess in the Scottish Highlands remained relatively high. While the lc-excess was usually not significantly different from zero at 15-20 cm soil depth in the studied podzols of the study site, soils studied by McCutcheon et al (2016) in a much drier environment (Dry Creek, Idaho) showed that the SW lc-excess from the surface down to −70 cm was significantly lower than zero. The high soil water storage contributes to the SW lc-excess dynamics shown in the hysteresis pattern for the relationship between SW lc-excess and PET 30 , which revealed that there was a delayed response of the SW lc-excess to the onset and offset of soil evaporation in spring and autumn, respectively.…”
Section: Evaporation Dynamics Within the Soil-plant-atmosphere Interfacementioning
confidence: 86%
See 2 more Smart Citations
“…Ehleringer and Dawson, 1992;Dawson et al, 2002;Volkmann et al, 2016;Rothfuss and Javaux, 2017), and identifying plant water sources (e.g. Brooks et al, 2010;Dawson and Ehleringer, 1991;Dawson and Simonin, 2011;Goldsmith et al, 2012;Evaristo et al, 2015;Hervé-Fernández et al, 2016;McCutcheon et al, 2017). A recent review by Sprenger et al (2016) 5 provides an extensive overview of isotope-based studies in the unsaturated zone.…”
mentioning
confidence: 99%